Methodology for assessing the reliability of GaN high-electron-mobility transistors - Gunawan, Anton. (2012)
The main motivation for this report is to study the degradation mechanisms which reduce the reliability of GaN HEMTs which in turn limit the performance of the devices in the long run and to establish a failure analysis methodology for GaN HEMTs to understand better the degradation mechanisms in the device. Basic device physics, device characterization and failure modes of GaN HEMTs would also be studied. The main objective of this project is to formulate the methodology to perform failure analysis on the AlGaN/GaN HEMT to observe the degradation of device. The important DC parameters were captured and evaluated to understand the degradation better to improve reliability in the future. The first thing that was done in the project was to determine the stress bias conditions for both operating lifetime (OL) and high reverse bias (HRB) at Tbase=35oC for the devices. It was found out that HRB was more degrading than the OL due to high electric field at the gate-drain side. The main study was about the OL and HRB tests at different temperatures after GDI (Gate Dielectric Isolation) and after CDI (Collector Diffusion Isolation) processes. The study of HRB after GDI process led the team to the discovery of abnormalities that caused the devices to breakdown. The study showed that degradation was relatively lesser in after CDI process as compared to after GDI process. The other study was about high temperature OL (HTOL) where it showed once again the effect of high temperature to accelerate degradation. The devices were degrading much faster as the temperature gets higher. In conclusion, the high temperature played a significant part to accelerate failures. From the defect analysis, it was found that the high electric field and trapping at different locations played major parts to degrade the device. Surface trapping was getting worse more as the temperature got higher. It would lead to a slower large-signal response time and restricted microwave power output as the drain current could not follow the applied ac gate signal. The failure analysis results were mostly in agreement with the established literatures and further device optimizations were still in the process to suppress this effect.